Representations of Pandemic and Climate Crisis in Greek Language – Impacts on Communication and Social Inequality - Tsitsanoudis-Mallidis, Nikoletta (Technical Annals, 2025)
This paper explores how various contemporary crises, such as the pandemic and the climate crisis, are reflected linguistically in public discourse. It investigates the representations of these crises within language, highlighting the significant impact that social transformations and phenomena have on linguistic expression. Central to the analysis is how such crises bring about notable shifts in word meanings, as familiar terms often acquire new, multifaceted connotations. A key aspect of the study is the examination of semantic changes in specific words, where known audio patterns and verbal structures are employed to convey altered meanings—sometimes in ways that may confuse recipients. Although mainstream media often promote an image of broad consensus, these semantic shifts are not always the result of natural language evolution among native speakers. Instead, they are frequently introduced in a top-down fashion, constructing a veiled reality. In this constructed reality, official narratives concerning economic, political, or social matters may obscure deeper truths, limiting public understanding of the actual crises they experience. Moreover, the study delves into how such linguistic redefinitions can weaken social protections and intensify social inequality. It also examines the impact of these shifts on education—particularly language education—by hindering students’ ability to engage critically with public discourse. The research material includes texts drawn from newspapers, television news broadcasts, and social media platforms. The study is grounded in the theoretical framework of Critical Discourse Analysis. Ultimately, the paper seeks to shed light on the wider social implications of these linguistic transformations and the challenges they present to education in times of societal crisis.